2020
DOI: 10.1097/mph.0000000000001991
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic Stem Cell Transplantation for Hepatitis-associated Aplastic Anemia Following Liver Transplantation for Nonviral Hepatitis: A Retrospective Analysis and a Review of the Literature by the Severe Aplastic Anemia Working Party of the European Society for Blood and Marrow Transplantation

Abstract: Hepatitis-associated aplastic anemia (HAAA) has been reported in 23% to 33% of patients who received orthotopic liver transplantation (LT) for acute liver disease of unknown origin (nonviral hepatitis). In this situation, hematopoietic stem cell transplantation (HSCT) might be a curative option. Here the authors report on 6 patients who received HSCT after LT for nonviral HAAA hepatitis. The outcomes were interpreted in the context of recently reported immune suppressive therapy (IST) outcomes in 8 patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…It has been suggested to take earlier approaches for patients when HAAA is developing (11). HSCT is preferred over immune suppressive therapy if an HLA-identical donor is available (12). Mori et al showed that allogeneic HSCT is safe with a low rate of transplant-related mortality (3).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested to take earlier approaches for patients when HAAA is developing (11). HSCT is preferred over immune suppressive therapy if an HLA-identical donor is available (12). Mori et al showed that allogeneic HSCT is safe with a low rate of transplant-related mortality (3).…”
Section: Discussionmentioning
confidence: 99%
“…1,2,11,13 The definitive treatment options for HAA are IST and HSCT, as in the case of acquired AA. [3][4][5][6]8,10,13 In children with acquired AA, HSCT has been recommended as the first-line therapy when HLAmatched related donor is available. 15,18 Multiple studies have reported 5-year survival rates of 90% or more in children who underwent HSCT with a matched related donor.…”
Section: Discussionmentioning
confidence: 99%
“…The course of hepatitis is unpredictable but AA is lethal if left untreated 1,2,11,13. The definitive treatment options for HAA are IST and HSCT, as in the case of acquired AA 3–6,8,10,13. In children with acquired AA, HSCT has been recommended as the first-line therapy when HLA-matched related donor is available 15,18.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations